Ibp, Inc. V. Alvarez: Has the Supreme Court Placed Employers on the Cutting Block? - Felton, Rachel (Journal of Law and Commerce, 2008)
According to the U.S. Supreme Court’s recent decision in IBP, Inc. v. Alvarez, walking that takes place during the workday may not only be good for employees’ health, but may also be good for their paychecks as any time employees spend walking after the donning of and prior to the doffing of required safety equipment must now be compensated under the Fair Labor Standards Act. While this is good news for employees, it is not good news to numerous employers for a several reasons. Based on the Supreme Court’s decision, employers are likely to face increases in liability and expenditures; increases in expenditures are most likely to take the form of litigation, labor, and restructuring costs, and will also include costs associated with implementing new workplace rules and policies regarding the donning and doffing of protective equipment and any related walking, and new timekeeping policies. Additionally, while not employer-specific problems, the application of the decision to the reality of the workplace creates opportunities for different compensation treatment of relatively similarly situated employees.